Critical variables for success in the technology adoption process in the framework of digital transformation - Salas Arbaiza, Cesar Enrique (2018)
The objective of the research is to identify the most representative variables considered critical for success in adoption processes in technology applicable to projects based on information technology and communications (ICT) in the framework of the digital transformation of organizations. For its identification, a cause-and-effect analysis is applied where the relationships that exist between ICT projects emerge and a categorization of technology projects for digital transformation framed in a classic evolution of projects, it is believed that before undertaking projects of this type it is important to consult this article in order to know in advance the variables that will guarantee successful projects.